Differential Immune Activating, Anti-Inflammatory, and Regenerative Properties of the Aqueous, Ethanol, and Solid Fractions of a Medicinal Mushroom Blend - Davis R; Taylor A; Nally R; Benson KF; Stamets P; Jensen GS (Dove Medical Press, 2020)
Renee Davis,1 Alex Taylor,1 Regan Nally,1 Kathleen F Benson,2 Paul Stamets,1 Gitte S Jensen2 1Fungi Perfecti, Olympia, WA 98507, USA; 2NIS Labs, Klamath Falls, OR 97601, USACorrespondence: Gitte S JensenNIS Labs, 1437 Esplanade, Klamath Falls, OR 97601, USATel +1 541 884-0112Fax +1403 441-5236Email gitte@nislabs.comPurpose: To compare three fractions of a medicinal mushroom blend (MMB), MyCommunity, on immune-activation, inflammation-regulation, and induction of biomarkers involved in regenerative functions.Methods: A seventeen-species MMB was sequentially extracted: first, saline solution at ambient temperature, followed by re-extraction of the solids in ethanol, and finally resuspension of the homogenized ethanol-insoluble solids in cell-culture media. Fractions were tested on peripheral blood mononuclear cells from three healthy donors. Immunostaining, flow-cytometry, and Luminex protein-arrays measured immune-cell activation and cytokine response. Dose-responses for induction of the CD69 early activation marker and individual cytokine and growth-factor responses for each donor were evaluated. The CD69 and the combined cytokine and growth-factor results were subjected to Non-metric Multidimensional Scaling (NMDS) and multivariate ordination to aid interpretation of the aggregate immune response and pairwise permutational MANOVA on a distance-matrix to evaluate statistical differences between treatments on pooled data from all donors.Results: Differential effects were induced by water-soluble, ethanol-soluble, and insoluble immunomodulatory compounds of the MMB. The aqueous and ethanol fractions upregulated expression of CD69 on all tested cell types. Monocyte-activation was correlated with the ethanol fraction, while NKT and non-NK non-T cell-activation was more closely correlated with the aqueous fraction. The solid fraction was the most potent inducer of Tumor Necrosis Factor-α, as well as the anti-viral cytokines interferon-γ, MCP-1 (CCL-2), MIP-1α (CCL-3), and MIP-1β (CCL-4), and induced G-CSF and b-FGF—growth-factors involved in regenerative functions—and the anti-inflammatory cytokine IL-1ra.Conclusion: The aqueous, ethanol, and insoluble compounds within MMB induced differential immune-activating, anti-inflammatory, and regenerative effects. This in vitro data suggests that, upon consumption, MMB may induce a concerted series of immunomodulatory events based on the differential solubility and bioavailability of the active constituents. These differential responses support both immune-activation and resolution of the host defense-induced inflammatory reactions, thus assisting a post-response return to homeostasis.Keywords: CD69, cytokines, growth factors, anti-viral peptides, medicinal mushrooms, mycelium, immune support, redundancy analysis, rda, multivariate ordination